275 Trends in the quality of myocardial infarction management in France: from evidence-based medicine to optimal clinical pathways. (23rd September 2015) - Hinglais, E; Goldstein, P; Ducasse, J L; Banaei-Bouchareb, L; Erbault, M; Riolacci-Dhoyen, N; Desplanques-Leperre, A; ,
Abstract : Background and Objectives: Evidence-based medicine has brought about a marked improvement in the management of myocardial infarction with ST elevation (STEMI). STEMI is a high-priority health issue. Coronary reperfusion techniques are highly effective especially when carried out promptly. Mortality rate at 1 month was 20% in 1990, 14% in 1995, 9% in 2000, and has been stable (about 7%) since 2005. The aim of practice improvement is to develop even better care pathways, for the benefit of more patients, to achieve even prompter reperfusion. However, mortality rate is probably not an appropriate indicator to measure the clinical impact of improvement initiatives as we are approaching the optimal rate, other factors are important, and new populations of patients are being recruited. Our objective was to develop indicators to measure quality within the patient's clinical pathway and clinical outcomes. Program: In France, emergency medicine services (EMS) and intensive care units in cardiology (ICUC) cooperate closely in urging the general public to call the EMS (call number 15) immediately in cases of chest pain. This helps guarantee swift arrival of EMS on scene and rapid treatment initiation. A national cooperative group, in association with HAS, has developed tools for a patient-centred quality programme that goes from practice improvement (implementation of consensus conference guidelines on optimal pre-hospital management) to practice measurement throughout care using clinical practice indicators (CPI). The quality dimensions are Efficacy (E) and Safety (S) (evidence-based) and Access (A) to best care (professional consensus). Results: Seven CPIs, shared by EMS and ICUC, were developed for the acute phase of the clinical pathway of MI patients: percentage of emergency calls, of direct transport by mobile intensive care units to ICUC (A, E, S), of reperfusions regardless of technique (E, A), delays in reperfusion for each technique (E, A), percentage of patients receiving appropriate antiplatelet treatment (E, S), and percentage of patients receiving analgesics (E). These CPIs form part of the databases dedicated to the 'STEMI—EMS—ICUC' pathway. Data analysis has revealed improvements in the percentage of calls to EMS, of direct transport to the ICUC and of reperfusions, and in delays to reperfusion therapy. Mortality rate is stable (see HAS 2009 report: 'Programme Infarctus 2007-2010, ensemble, améliorons la prise en charge de l'infarctus du myocarde', Bilan 2009. Etape 1, de la douleur à la reperfusion - Etape 2, de la reperfusion à la sortie de l'hôpital - Etape 3, suivi post infarctus après la sortie de l'hôpital.). In an analysis of three different databases relating to catchment areas with different constraints and medical demographics, results were similar despite the different ways in which guidelines were implemented, thus highlighting the clinical relevance of these standardised CPIs. An enlarged concatenation should enable better modelling of items needing improvement and the selection of the most relevant indicators for monitoring the clinical impact of improvement initiatives. Discussion and Conclusion: The use of CPIs to circumscribe the patient's care pathway improved quality of care, confirming the robustness of our model. A global approach to quality supported by health professionals, patients and health organisations enables translation of treatments with proven efficacy in clinical trials on selected patients into the 'greatest benefit for the greatest number' in real life. The CPIs developed for the various steps of a clinical pathway—that have been established, implemented and analysed with the professionals concerned - can be used to monitor and guarantee quality of care, thus reconciling public health and evidence-based medicine. The percentage of beneficiaries is an indicator of clinical impact and mortality rate is an indicator of absence of drift. However, there is a need for innovative CPIs in order to include post acute phase care, risk factors, and quality of life into the assessment of the patient's clinical pathway. Contexte et objectifs: La médecine fondée sur les preuves a contribué à améliorer de façon spectaculaire la prise en charge de l'infarctus ST+ (IDM), enjeu de santé prioritaire: les différentes thérapeutiques de reperfusion coronaire sont d'une efficacité remarquable, encore meilleure si réalisées au plus vite. La mortalité à 1 mois est passée de 20% en 1990, 14% (1995), à 9% (2000), pour se stabiliser aux alentours de 7% depuis 2005. Des filières de soins optimales, pour plus de patients, pour une reperfusion encore plus rapide, constituent un objectif majeur d'amélioration des pratiques, dont l'impact clinique sera probablement difficilement objectivable par la mortalité: approche des taux optimaux, autres facteurs influant, recrutement de nouveaux malades. L'objectif de ce travail est de développer des indicateurs pour mesurer la qualité des soins et les résultats cliniques. Programme: La médecine d'urgence et la cardiologie coopèrent étroitement en France pour sensibiliser la population à appeler le n° d'urgence « 15 » et réduire les délais de prise en charge. Pour définir le parcours de soins optimal, le groupe national de coopération, en lien avec la HAS, a élaboré les outils d'un programme intégré centré sur le patient: depuis l'amélioration des pratiques - conférence de consensus (CdC): prise en charge et parcours optimal en France avant l'arrivée en cardiologie—à la mesure des pratiques et de l'impact clinique—indicateurs de pratique clinique (IPC) sur le parcours patient. Résultats: CdC comme IPC couvrent les champs Qualité-ESA: Efficacité (E) Sécurité (S), de niveaux de preuve élevés, et Accès (A), consensus professionnel. Sept IPC partagés bornent les pratiques à la phase aiguë: % d'appel au 15, % d'orientation directe en USIC (A, E, S), % de reperfusion, quelle qu'en soit la technique (E, A), délai de reperfusion par technique (E, S, A), % d'antiagrégants plaquettaires appropriés (E, S), % d'antalgiques (E). Ces IPC ont été intégrés aux bases de données dédiées aux filières IDM -Urgence-Cardiologie. Ils ont montré que (i) une amélioration dans le temps des IPC—appel au 15, orientation en USIC, % et délais de reperfusions - (ii) une mortalité stable (cf rapport public HAS—groupe de coopération 2009: 'Programme Infarctus 2007-2010, ensemble, améliorons la prise en charge de l'infarctus du myocarde', Bilan 2009. Etape 1, de la douleur à la reperfusion - Etape 2, de la reperfusion à la sortie de l'hôpital - Etape 3, suivi post infarctus après la sortie de l'hôpital.). L'uniformisation des IPC et la recherche d'indicateurs d'impact encouragent la mise en commun de différentes bases. Dans 3 observatoires de pratiques - de contraintes géographiques et démographies médicales différentes - l'homogénéité des résultats des IPC au regard des différentes organisations déployées pour implémenter la CdC, conforte la pertinence clinique des indicateurs. La concaténation élargie des IPC permettra de mieux modéliser les points à améliorer et de sélectionner les indicateurs les plus pertinents pour suivre l'impact clinique des démarches d'amélioration. Discussion et conclusion: Des parcours patient marqués par des IPC Qualité-ESA permettent d'améliorer la qualité des soins dans la vraie vie, ce qui confirme la robustesse du modèle proposé. Cette approche globale de la qualité portée par les professionnels de santé, les patients et les organisations sanitaires, permet d'appliquer dans la pratique quotidienne, au bénéfice du plus grand nombre, les traitements d'efficacité démontrée par les essais cliniques sur des patients sélectionnés. Des IPC Qualité-ESA sur les étapes clés – définis, recueillis et analysés en lien avec les professionnels – permettent de suivre et de garantir la qualité des soins, réconciliant dans la mise en œuvre, santé publique et médecine fondée sur les preuves. Si le nombre de patients bénéficiaires constitue sans nul doute un indicateur d'impact clinique, si le suivi de la mortalité doit garantir l'absence de dérive, demeurent à identifier des indicateurs d'impact clinique novateurs, intégrant également la prise en charge après la phase aiguë, la maitrise des facteurs de risque et la qualité de vie.